Enhancing Elementary Students’ Learning Outcomes through Digital Comic-Based Media: A Systematic Literature Review - Mia Saputri; Junaidi; Yasinta Mahendra (Universitas Pendidikan Ganesha, 2025)
The use of instructional media represents an important innovation for creating more engaging, interactive, and comprehensible learning experiences for elementary students. However, its implementation remains limited due to constraints in time, cost, and teachers’ technical capacity in media development. This study aims to analyze the effectiveness of digital comic-based learning media in enhancing elementary students’ learning outcomes. The research employed a Systematic Literature Review (SLR) method utilizing the Google Scholar database. The search process involved the combination of the keywords “digital comic media,” “learning outcomes,” and “elementary school,” restricted to publications from 2020 to 2024. From an initial pool of 2,050 documents, ten articles met the inclusion and methodological quality criteria for in-depth analysis. The collected data were thematically analyzed based on the empirical findings of each study. The results reveal that digital comic-based media are effective in improving students’ learning outcomes by presenting contextual visualizations, motivating narratives, and interactive elements that strengthen conceptual understanding, creativity, and learning engagement. These findings imply that digital comic-based learning media can serve as a strategic alternative for fostering effective 21st-century learning and improving the overall quality of elementary education.